Study on Applicability of Xin'anjiang Model and Tank Model in Flood Forecasting in Majiagou Reservoir - MA Jinghang; XIAN Yongcai; HE Xueping; LIU Ming; HAN Muyuan; DU Bailin; RUAN Bingnan; XU Liujia; WU Lei (Renmin Zhujiang)
Flood forecasting is one of the important non-engineering flood control measures and is the main basis for flood control command and decision-making.In order to avoid the uncertainty of the prediction results of a single model,the Majiagou Reservoir in Chenggu County was taken as the object to simulate the daily runoff and flood process from 2019 to 2021 by using the Xin'anjiang model and tank model respectively,and the simulation results and accuracy of the two models were compared by using the model parameters calibrated and optimized by the genetic algorithm.In the daily runoff simulation,the simulation effect of the tank model is better than that of the Xin'anjiang model,with a relative error of flood volume of less than 16%,a relative error of flood peak of less than 4%,a difference of peak time of less than 1 h,and a Nash-Sutcliffe efficiency coefficient of greater than 0.58,all of which meet the evaluation accuracy requirements of the Standard for Hydrological Information and Hydrological Forecasting,and the simulation effect of deluge in the reservoir is ideal.In the flood process simulation,the difference of peak time between the two models is similar;the simulation effect of the Xin'anjiang model is smoother,and the flood volume and flood peak simulated by the tank model are closer to the measured flow process.On the whole,the tank model is more suitable for flood forecasting in Majiagou Reservoir than the Xin'anjiang model.